Global West, American frontier : travel, empire, and exceptionalism from Manifest Destiny to the Great Depression - Wrobel, David M.; ebrary, Inc. (Albuquerque : University of New Mexico Press, 2013)
"This thoughtful examination of a century of travel writing about the American West overturns a variety of popular and academic stereotypes. Looking at both European and American travelers' accounts of the West, from de Tocqueville's Democracy in America to William Least Heat-Moon's Blue Highways, David Wrobel offers a counternarrative to the nation's romantic entanglement with its western past and suggests the importance of some long-overlooked authors, lively and perceptive witnesses to our history who deserve new attention.Prior to the professionalization of academic disciplines, travel writers found a wide and respectful audience for their reports on history, geography, and the natural world, in addition to reporting on aboriginal cultures before there was such a discipline as anthropology. In recent decades travel writers have not received much respect in the academy, but Wrobel rescues this lively genre, demonstrating that travel writers offered an understanding of the West considerably more complex than the notion of the mythic West promoted to support Manifest Destiny in the nineteenth century and American exceptionalism in the twentieth"--
part one. The global West of the nineteenth century -- part two. The American frontier of the twentieth century.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Travel writing -- Historiography; West (U.S.) -- Description and travel; West (U.S.) -- Historiography; West (U.S.) -- Public opinion; Electronic books